PEMANFAATAN TEKNOLOGI AUGMENTED REALLITY (AR) UNTUK MEMBANTU PROSES PEMBELAJARAN DI SD 03 BILAH BARAT - Angga Putra Juledi; Marnis Nasution; Deci Irmayani; Fitri Aini Nasution; Syaiful Zuhri Harahap (PT.JNDI, JURNAL BIMA, 2025)
The use of Augmented Reality (AR) in education can enhance students' understanding of concepts and increase their learning motivation. This study aims to implement AR in learning at SD 03 Bilah Barat through socialization and workshops. The results show that AR makes learning more interactive, helps students grasp abstract concepts more easily, and boosts motivation. However, challenges such as limited technology and teacher readiness remain obstacles. Based on the success indicators, this activity achieved its set targets. AR has great potential to improve learning quality, but further support is needed for its sustainability.